Pemberian ASI eksklusif tidak berhubungan dengan stunting pada anak usia 6–23 bulan di Indonesia - Bunga Astria Paramashanti; Hamam Hadi; I Made Alit Gunawan (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2015)
ABSTRACTBackground: Stunting in children is one of public health problem in Indonesia. Stunting is a serious problem because it is linked with the quality of human capital in future. Objectives: To determine the association between exclusive breastfeeding practice and stunting in young children 6 – 23 months in Indonesia.Methods: This study used a cross-sectional design. Data was obtained from Basic Health Research (Riskesdas) 2013. Riskesdas 2013 used multistage cluster sampling. Subject in this study was 6.956 young children 6 – 23 months in Indonesia which was selected purposively. Data was analyzed by using descriptive analysis, chi-square, and multiple logistic regression by adjusting the sampling weight for survey analysis.Results: Exclusive breastfeeding was protective against stunting, but the result was not significant both for exclusive breastfeeding >6 months (OR=0,99, 95% CI: 0,63–1,59) and exclusive breastfeeding 4-<6 bulan (OR=0,93, 95% CI: 0,63–1,39). Young children with low birth weight history had higher risk to become stunting (OR=1,77, 95% CI: 1,33–2,37). Household economic status which were very poor (OR=1,96, CI: 1,53–2,52), poor (OR=1,62, 95% CI:1,30–2,03) and middle (OR=1,32, 95% CI: 1,06–1,64) were also associated with the risk of stunting.Conclusions: Exclusive breastfeeding is not the only factor contributing to stunting in children. Optimal complementary feeding practice should also be the focus of intervention. Improvement in nutritional status since the preconception and during the pregnancy, and household economy status may reduce stunting problem in children.KEYWORDS: stunting, exclusive breastfeeding, feeding practice, growth ABSTRAKLatar belakang: Stunting pada anak-anak merupakan salah satu masalah kesehatan masyarakat yang utama di Indonesia. Stunting menjadi masalah yang serius karena dikaitkan dengan kualitas sumber daya manusia di kemudian hari.Tujuan: Untuk mengetahui hubungan antara praktik pemberian ASI eksklusif dan stunting pada anak usia 6 – 23 bulan di Indonesia.Metode: Desain penelitian ini adalah cross-sectional. Data didapatkan dari hasil riset kesehatan dasar (Riskesdas) 2013. Teknik pengambilan sampel pada Riskesdas 2013 adalah multistage cluster sampling. Subjek pada penelitian ini berjumlah 6.956 anak usia 6 – 23 bulan di Indonesia yang dipilih secara purposive. Data dianalisis dengan menggunakan analisis deskriptif, chi-square dan regresi logistik berganda dengan mempertimbangkan sampling weight untuk analisis survei.Hasil: ASI eksklusif bersifat protektif terhadap kejadian stunting pada anak, namun hasilnya tidak signifikan, baik untuk ASI eksklusif >6 bulan (OR=0,99, 95% CI 0,63–1,59) maupun ASI eksklusif 4-<6 bulan OR=0,93, 95% CI: 0,63–1,39). Anak yang lahir dengan berat badan lahir rendah (BBLR) memiliki risiko yang lebih tinggi untuk menjadi anak yang stunting (OR=1,77, 95% CI: 1,33–2,37). Status ekonomi rumah tangga sangat miskin (OR=1,96, 95% CI: 1,53–2,52), miskin (OR=1,62, 95% CI: 1,30–2,03) danmenengah (OR=1,32, 95% CI: 1,06–1,64) masing-masing berkontribusi terhadap peningkatan risiko stunting pada anak.Kesimpulan: ASI eksklusif bukanlah satu-satunya faktor yang berkontribusi terhadap kejadian stunting pada anak. Pemberian MPASI yang optimal juga harus diperhatikan. Perbaikan status gizi sejak masa prekonsepsi dan selama kehamilan, serta status ekonomi rumah tangga diharapkan mampu menurunkan kejadian stunting pada anak.KATA KUNCI: stunting, ASI eksklusif, praktik makan, pertumbuhan